2020
DOI: 10.31943/teknokom.v3i1.50
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Statisik Perbandingan Manipulasi Suara Dan Suara Asli Menggunakan Teknik Audio Forensik

Abstract: Kejahatan digital yang semakin beragam menuntut Tim ahli forensik untuk meningkatkan pengetahuan dalam pengungkapan kasus didalam dunia digital. Teknik audio forensik merupakan bagian dari ilmu digital forensik, yang lebih fokus pada analisa suara serta berbagai manipulasi didalamnya yang harus dapat dibuktikan di persidangan. Salah satu tantangan yang dihadapi dalam mengungkap kejahatan melalui audio yaitu adanya manipulasi suara yang berbeda dengan suara sumber atau pelaku. Analisa yang dilakukan menggunakan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The audio recorder also underwent a change from an analog phonograph recorder to a digital recorder that was not shaped like a recorder [7]. From several previous studies, voice manipulation has been carried out to change the identity of the original voice with various anti-forensic methods such as the use of a voice changer with a telephone effect conducted by A.B Baskoro [8] in 2020, the use of a voice changer with the effects of aliens, robots and zombies conducted by Rusydi Umar [9] in 2019, increasing 20% audio speed conducted by Yasep Azzery [10] in 2020 and the use of MDCT audio conducted by Tao B [11] in 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The audio recorder also underwent a change from an analog phonograph recorder to a digital recorder that was not shaped like a recorder [7]. From several previous studies, voice manipulation has been carried out to change the identity of the original voice with various anti-forensic methods such as the use of a voice changer with a telephone effect conducted by A.B Baskoro [8] in 2020, the use of a voice changer with the effects of aliens, robots and zombies conducted by Rusydi Umar [9] in 2019, increasing 20% audio speed conducted by Yasep Azzery [10] in 2020 and the use of MDCT audio conducted by Tao B [11] in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…However, both studies did not use the ANOVA method as an analysis in identifying authenticity in sound recordings. Yasep Azzery [10] conducted a study of manipulating sound recordings by increasing the audio speed by 20%. By analyzing the pitch, formant, and spectrogram using the ANOVA approach, it can be concluded that the sound of the manipulated evidence recording and the recorded voice of the subject as a comparison are not identical.…”
Section: Introductionmentioning
confidence: 99%